Experimental study on the energy dissipation mechanism of bolted rock under dynamic loading - Peng-qi Qiu; Wen-wei Wang; Kai Wang; Xiao-qiang Zhang; Jian-guo Ning; Chun-li Zhao; Yu-long Jiang; Jiang-dong Zheng; Ting-ting Cai; Xiaoyong Yang (Scientific Reports)
Abstract The impact failure response characteristics of rock specimens and bolted rock specimens under different impact dynamic loads were studied by Split Hopkinson pressure bar (SHPB). By comparing the time history laws of incident energy, reflection energy, transmission energy and dissipation energy in the process of rock impact failure in combination with the dynamic strain characteristics of bolts and rock, the energy dissipation mechanism of bolted rock under impact loading was obtained. The design idea of surrounding rock bolt support in a dynamic loading roadway was proposed. The results show that ① When the impact velocity of the bullet is 7.1 m/s, 8.1 m/s and 8.9 m/s, the “EPRD” (effectiveness for a given period to resistance dynamic load) of bolted rock are 158 μs, 139 μs and 121 μs, respectively. The increase in impact velocity shortens the “EPRD” of bolted rock and accelerates the failure of bolted rock. ② The impact dynamic load energy of bolted rock is stored in the form of strain energy in the "cooperative deformation stage". The impact dynamic load energy of the "non-cooperative deformation stage" is dissipated by the pore initiation and development of the rock matrix, new surface, new crack and shear slip deformation between the bolt and rock. The impact dynamic load energy of the “failure stage” primarily acts on the broken rock. ③ The dissipation energy is an inherent property of bolted rock and has nothing to do with the impact dynamic load. The influence of the impact dynamic load on the deformation of the roadway surrounding rock can be reduced by increasing the "anti-energy" coefficient of the surrounding rock.